Virome Analysis of Aphid Populations That Infest the Barley Field: The Discovery of Two Novel Groups of Nege/Kita-Like Viruses and Other Novel RNA Viruses - Kondo, Hideki; Fujita, Miki; Hisano, Hiroshi; Hyodo, Kiwamu; Andika, Ida Bagus; Suzuki, Nobuhiro (Frontiers in Microbiology, 2020)
Aphids (order Hemiptera) are important insect pests of crops and are also vectors of many plant viruses. However, little is known about aphid-infecting viruses, particularly their diversity and relationship to plant viruses. To investigate the aphid viromes, we performed deep sequencing analyses of the aphid transcriptomes from infested barley plants in a field in Japan. We discovered virus-like sequences related to nege/kita-, flavi-, tombus-, phenui-, mononega-, narna-, chryso-, partiti-, and luteoviruses. Using RT-PCR and sequence analyses, we determined almost complete sequences of seven nege/kitavirus-like virus genomes; one of which was a variant of the Wuhan house centipede virus (WHCV-1). The other six seem to belong to four novel viruses distantly related to Wuhan insect virus 9 (WhIV-9) or Hubei nege-like virus 4 (HVLV-4). We designated the four viruses as barley aphid RNA virus 1 to 4 (BARV-1 to -4). Moreover, some nege/kitavirus-like sequences were found by searches on the transcriptome shotgun assembly (TSA) libraries of arthropods and plants. Phylogenetic analyses showed that BARV-1 forms a clade with WHCV-1 and HVLV-4, whereas BARV-2 to -4 clustered with WhIV-9 and an aphid virus, Aphis glycines virus 3. Both virus groups (tentatively designated as Centivirus and Aphiglyvirus, respectively), together with arthropod virus-like TSAs, fill the phylogenetic gaps between the negeviruses and kitaviruses lineages. We also characterized the flavi/jingmen-like and tombus-like virus sequences as well as other RNA viruses, including six putative novel viruses, designated as barley aphid RNA viruses 5 to 10. Interestingly, we also discovered that some aphid-associated viruses, including nege/kita-like viruses, were present in different aphid species, raising a speculation that these viruses might be distributed across different aphid species with plants being the reservoirs. This study provides novel information on the diversity and spread of nege/kitavirus-related viruses and other RNA viruses that are associated with aphids.